جماليات الخطاب في أدب الأطفال مقاربة في الرؤية والتّشكيل - شادلي, عمر (جامعة الوادي - University of Eloued, 2021)
ملخص: تسعى هذه الورقة البحثية إلى بيان أهمية أدب الأطفال في محاكاة هذا الجسد العقيم، والارتقاء به ليكون ذا عقل خلاق. وهذا جلي من خلال المقاربة التي تمسّ الرؤية الاستشرافية مراعية العمل الإبداعي لكونه يحمل أيقونات معرفية من القصص بداية من الحكاية التي تحمل في ثناياها بعد تعليمي. وبما أنّ للمخيال من أهمية في القصص الحكائي أردنا أن نقف على بعض النّصوص الحكائية لما فيها من مغزى علمي أخلاقي هادف يقتفي من أثره الطفل المغزى، وهذا يتمّ بعد أن نصّرح بخياله مّما يكسبهم القدرة على التفكير والابتكار والإبداع الخلاق، ولذلك يعتبر الخيال دافع يكشف نتيجة تملك عقولهم القدرة على محدودية الواقع. Abstract: This paper seeks to demonstrate the importance of children's literature in the simulation of this sterile body and to make it a creative mind. This is evident in the approach that touches the prospective vision، taking into account the creative work that carries the icons of the stories، especially the stories that have an educational purpose. Since the imagination is of importance in the stories of history، we aim to study some of the texts of history thanks to the moral significance of the desired scientific trace of the meaning of the child. And this can be done after we declare his imagination which gives him the ability to think، innovate and create. The imagination is a revealing motive of the result in the limited reality.
مقال
Keywords: أدب الأطفال . الخيال. الرؤية. التشكيل. القصة; children's littérature. Imagination. Vision. Configuration. Story.